Application of Games Based Learning Based on Culturally Responsive Teaching to Improve Mathematics Learning Outcomes - Sulistyowati, Prihatin; Rahmawati, Risa Arum; Rofika, Nadia (Actual Insight, 2025)
This study aims to improve the mathematics learning outcomes of grade II elementary school students through the implementation of the Game-Based Learning (GBL) model integrated with the Culturally Responsive Teaching (CRT) approach. The background of this research is the low level of student achievement and engagement in mathematics learning, which often lacks contextual and culturally relevant content. The combination of GBL and CRT is considered effective because it creates an active, enjoyable, and meaningful learning environment while connecting learning materials to students’ cultural backgrounds. This Classroom Action Research employed the Kurt Lewin model, conducted in two cycles consisting of pre-cycle, Cycle I, and Cycle II stages, involving 28 students of grade IIA at SDN Bandungrejosari 3 Malang City. Data were collected using observation sheets, documentation, and mathematics learning outcome tests. The results showed a significant improvement in students' learning outcomes, with mastery learning increasing from 38.46% in the pre-cycle to 67.85% in Cycle I, and reaching 85.71% in Cycle II. The integration of GBL and CRT not only enhanced student achievement but also increased students' activeness, participation, and enthusiasm during mathematics lessons. These findings indicate that the combined application of the GBL model and CRT approach is effective in improving mathematics learning outcomes in elementary schools.